Chemsex among men who have sex with men (MSM) in Yangon, Myanmar: Prevalence, practices, and associated risk factors - Naung Latt Htun; Myo-Myo Mon; Kyaw Soe Thant; Phyu Phyu Kyaw (PLoS ONE, 2026)
Introduction Chemsex is the intentional use of psychoactive substances to facilitate, enhance, or prolong sexual encounters. It is notably common among men who have sex with men (MSM), contributing to high-risk sexual behaviors. However, limited research has focused on chemsex among MSM in Myanmar. This study aimed to assess the prevalence, practices, and associated risk factors of chemsex among MSM in Yangon, Myanmar. Materials and methods Between December 2024 and January 2025, a cross-sectional online survey was conducted among MSM aged 18 and older living in Yangon. Participants were recruited through social media platforms, including Facebook and Telegram, as well as dating apps. Data were collected using the KoboCollect platform and analyzed in SPSS. Descriptive statistics summarized demographic and behavioral data, and multivariate analyses identified factors associated with chemsex. Results The study included 415 MSM participants with a mean age of 30.1 years. The majority (71.3%) were between 18 and 34 years old. Most identified as gay (76%), had a university or postgraduate degree (62%), and 60% were employed. Approximately 26% reported engaging in chemsex at some point, with 20.7% having done so within the past six months. The most commonly reported substances were methamphetamine (69.8%), poppers (33.7%), and cannabis (19.8%). Injection and inhalation were the most common routes of administration. Chemsex sessions mostly took place in hotels (76.7%) and homes (54.7%), and for nearly half of participants, sessions lasted between 4 and 12 hours. Only 10% reported consistent condom use during chemsex, while group sex was frequent – about 40% engaged with 4–5 partners, and nearly 60% participated in threesomes. Chemsex within the last 14 days was reported by 46.5%. Factors significantly associated with chemsex included identifying as gay (aOR = 3.0, 95% CI:1.5–5.9, p = 0.001), smoking (aOR = 2.8, 95% CI:1.2–4.0, p = 0.006), participation in group sex (aOR = 4.0, 95% CI: 2.4–6.6, p < 0.001), and having multiple partners (aOR = 3.3, 95% CI:1.7–6.3, p < 0.001). Conclusion Chemsex prevalence among MSM in Yangon is alarmingly high and associated with risky behaviors. There is an urgent need for targeted interventions that focus on education, harm reduction, and improved access to MSM-specific health services.